Multimodality endoscopic eradication for neoplastic Barrett oesophagus: results of an European multicentre study (EURO-II). Issue 4 (2nd March 2015) - Phoa, K Nadine; Pouw, Roos E; Bisschops, Raf; Pech, Oliver; Ragunath, Krish; Weusten, Bas L A M; Schumacher, Brigitte; Rembacken, Bjorn; Meining, Alexander; Messmann, Helmut; Schoon, Erik J; Gossner, Liebwin; et al.
Abstract : Objective: Focal endoscopic resection (ER) followed by radiofrequency ablation (RFA) safely and effectively eradicates Barrett's oesophagus (BO) containing high-grade dysplasia (HGD) and/or early cancer (EC) in smaller studies with limited follow-up. Herein, we report long-term outcomes of combined ER and RFA for BO (HGD and/or EC) from a single-arm multicentre interventional study. Design: In 13 European centres, patients with BO≤12 cm with HGD and/or EC on 2 separate endoscopies were eligible for inclusion. Visible lesions (<2 cm length; <50% circumference) were removed with ER, followed by serial RFA every 3 months (max 5 sessions). Follow-up endoscopy was scheduled at 6 months after the first negative post-treatment endoscopic control and annually thereafter. Outcomes: complete eradication of neoplasia (CE-neo) and intestinal metaplasia (CE-IM); durability of CE-neo and CE-IM (once achieved) during follow-up. Biopsy and resection specimens underwent centralised pathology review. Results: 132 patients with median BO length C3M6 were included. After entry-ER in 119 patients (90%) and a median of 3 RFA (IQR 3–4) treatments, CE-neo was achieved in 121/132 (92%) and CE-IM in 115/132 patients (87%), per intention-to-treat analysis. Per-protocol analysis, CE-neo and CE-IM were achieved in 98% and 93%, respectively. After a median of 27 months following the first negative post-treatment endoscopic control, neoplasia and IM recurred in 4% and 8%, respectively. Mild-to-moderate adverse events occurred in 25 patients (19%); all managed conservatively or endoscopically. Conclusions: In patients with early Barrett's neoplasia, intensive multimodality endotherapy consisting of ER combined with RFA is safe and highly effective, and the treatment effect appears to be durable during mid-term follow-up. Trial registration number: NTR 1211, http://www.trialregister.nl .